Secondary battery and electric device

By regulating the particle size of lithium manganese iron oxide, the ratio of manganese to iron, the thickness of the conductive polymer coating layer and the groove depth of the positive electrode active material layer, a specific relationship of the cathode plate is formed, which solves the problem of cycling of lithium manganese iron oxide secondary batteries. Constant voltage charging eliminates long-term problems and significantly improves gas production and cycle performance.

CN119361790APending Publication Date: 2025-01-24SUNWODA MOBILITY ENERGY TECHNOLOGY CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411303088.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The lithium iron manganese oxide secondary battery has a long charging time at the constant voltage, which leads to problems such as electrolyte decomposition, gas production bloating and circulating diving.

Method used

Through reasonable regulation of the particle size, manganese iron ratio, surface high dynamic guideline polymer cover layer, and the depth of the grooves in the grooves of the grooves of the grooves of the manganese iron lithium oxide containing MG elements and/or TI elements The parameter meets the specific relationship, forming a positive pole film of the coated layer of conductive polymer and the groove structure.

Benefits of technology

A significant reduction of the reconstruction of the cycle of the secondary battery, improved the gas production performance and cycle performance, and reduced the cracking of the coating of the positive pole.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005048397080000101
    Figure BDA0005048397080000101
  • Figure BDA0005048397080000111
    Figure BDA0005048397080000111
Patent Text Reader

Abstract

The invention provides a secondary battery and electric equipment. By reasonably regulating and controlling the particle size and the manganese-iron ratio of the manganese-iron-lithium oxide containing the Mg element and / or the Ti element, the thickness of the surface high-dynamics conductive polymer coating layer and the depth of the groove in the positive electrode active material layer, the parameters meet a specific relational expression, and the cycle constant-voltage charging duration of the secondary battery is remarkably shortened; and the gas production performance and the cycle performance of the secondary battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, in particular to a secondary battery and an electrical device. Background Art

[0002] Manganese iron lithium oxide is a positive electrode material for secondary batteries, with good safety and stability. On the basis of iron lithium oxide, it is doped with manganese to increase the charging voltage, which can increase the energy density by more than 15%, and the cost is basically the same as that of iron lithium oxide. However, manganese iron lithium oxide has poor intrinsic kinetic performance, and it takes a long time of constant voltage charging to fully charge the battery, and the constant voltage charging capacity accounts for a high proportion. The excessively long constant voltage charging stage at high potential will cause a large amount of decomposition of the electrolyte, resulting in gas production and swelling of the manganese iron lithium secondary battery, which in turn causes problems such as secondary battery cycle diving. Summary of the invention

[0003] The purpose of the present application is to provide a secondary battery and an electrical device to reduce the cyclic constant voltage charging time of a secondary battery using manganese iron lithium oxide as a positive electrode active material, thereby improving the gas production performance and cycle performance of the secondary battery.

[0004] To achieve the above-mentioned object, in a first aspect of the present application, a secondary battery is provided, comprising a positive electrode plate, wherein the positive electrode plate comprises a current collector and a positive electrode active material layer disposed on at least one side of the current collector, wherein the positive electrode active material layer comprises a positive electrode active material, wherein the positive electrode active material comprises manganese iron lithium oxide and a coating layer comprising a conductive polymer disposed on at least a portion of the surface of the manganese iron lithium oxide, wherein the manganese iron lithium oxide contains Mg element and / or Ti element;

[0005] A groove is provided on the surface of the positive electrode active material layer away from the current collector along the thickness direction of the positive electrode sheet;

[0006] The positive electrode sheet satisfies: 0.03≤K≤0.37, K=δ×P / D / W 2 ;

[0007] Wherein, Dμm is the Dv50 of the manganese iron lithium oxide;

[0008] P μm is the depth of the groove in the positive electrode active material layer;

[0009] δμm is the thickness of the coating layer;

[0010] W is the molar ratio of manganese atoms to iron atoms in the manganese iron lithium oxide.

[0011] As an implementation scheme of the present application, 0.7≤D≤1.3.

[0012] As an implementation scheme of the present application, 13≤P≤17.

[0013] As an embodiment of the present application, 0.002≤δ≤0.006.

[0014] As an implementation scheme of the present application, 0.4≤W≤1.5.

[0015] As an embodiment of the present application, the conductive polymer includes at least one of polyethylene succinate, polyethylene oxide, polyethylene glycol imine, and polypyrrole.

[0016] As an embodiment of the present application, the manganese iron lithium oxide contains Mg element and Ti element, the content of the Mg element is Appm, the content of the Ti element is B ppm, and satisfies: A / B≤10.3.

[0017] As an embodiment of the present application, the content of the Mg element is A ppm, 2400≤A≤3100.

[0018] As an embodiment of the present application, the content of the Ti element is B ppm, 300≤B≤1800.

[0019] A second aspect of the present application provides an electrical device, wherein the electrical device comprises the secondary battery described in the first aspect of the present application.

[0020] Compared with the prior art, the beneficial effects of this application are:

[0021] The present application provides a secondary battery using manganese iron lithium oxide as a positive electrode active material. The present application reasonably regulates the particle size, manganese iron ratio, thickness of the surface high-dynamic conductive polymer coating layer and depth of the grooves in the positive electrode active material layer of the manganese iron lithium oxide containing Mg and / or Ti elements, so that the above parameters satisfy a specific relationship, significantly reduces the cyclic constant-voltage charging time of the secondary battery, and improves the gas production performance and cycle performance of the secondary battery. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0023] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0024] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0025] The reagents or instruments used in this application without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.

[0026] An embodiment of the present application provides a secondary battery, the secondary battery comprising a positive electrode plate, the positive electrode plate comprising a current collector and a positive electrode active material layer disposed on at least one side of the current collector, the positive electrode active material layer comprising a positive electrode active material, the positive electrode active material comprising manganese iron lithium oxide and a coating layer containing a conductive polymer disposed on at least a portion of the surface of the manganese iron lithium oxide, the manganese iron lithium oxide containing Mg element and / or Ti element;

[0027] A groove is provided on the surface of the positive electrode active material layer away from the current collector along the thickness direction of the positive electrode sheet;

[0028] The positive electrode sheet satisfies: 0.03≤K≤0.37, K=δ×P / D / W 2 ;

[0029] Wherein, Dμm is the Dv50 of the manganese iron lithium oxide;

[0030] P μm is the depth of the groove in the positive electrode active material layer;

[0031] δμm is the thickness of the coating layer;

[0032] W is the molar ratio of manganese atoms to iron atoms in the manganese iron lithium oxide.

[0033] The inventors of the present application have discovered that the fundamental reason why the secondary battery using lithium iron manganese oxide as the positive electrode active material has a long cycle charging time is that the intrinsic kinetic performance of lithium iron manganese oxide is poor. By reasonably regulating the particle size, manganese-iron ratio, thickness of the surface high-kinetic conductive polymer coating layer and depth of the grooves in the positive electrode active material layer of the lithium iron manganese oxide containing Mg and / or Ti elements, making these parameters satisfy the relationship described in the present application, the kinetic performance of the secondary battery can be significantly improved, thereby reducing the cycle charging time and ultimately improving the gas production performance and cycle performance of the secondary battery.

[0034] In some embodiments, the Dv50 of the manganese iron lithium oxide is Dμm, 0.7≤D≤1.3. Exemplarily, the Dv50 of the manganese iron lithium oxide can be any one of 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, or a range between any two values. The Dv50 of manganese iron lithium oxide has better kinetic performance within the above range, thereby reducing the cycle constant voltage charging time of the secondary battery, while reducing the problem of cracking of the positive electrode coating, and providing the cycle performance and gas production performance of the secondary battery.

[0035] In some embodiments, the depth of the groove in the positive electrode active material layer is P μm, 13 ≤ P ≤ 17. Exemplarily, the depth of the groove in the positive electrode active material layer can be any one of 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, or a range between any two values. When the depth of the groove in the positive electrode active material layer is within this range, the wettability of the manganese iron lithium positive electrode plate can be improved, thereby improving the reaction kinetics of the manganese iron lithium phosphate secondary battery from the plate level.

[0036] In some embodiments, the thickness of the coating layer is δμm, 0.002≤δ≤0.006. Exemplarily, the thickness of the coating layer can be any one of 0.002μm, 0.003μm, 0.004μm, 0.005μm, 0.006μm, or a range between any two values. The thickness of the coating layer containing a conductive polymer is within the above range, which can improve the kinetic properties of the manganese iron lithium oxide positive electrode, reduce its polarization during the charge and discharge process, and reduce the duration of constant voltage charging. In addition, the conductive polymer coating can avoid direct contact between the positive electrode material and the electrolyte, inhibiting the circulation of Mn 2+ dissolution, thereby effectively improving the cycle life of manganese iron lithium oxide batteries.

[0037] In some embodiments, the molar ratio of manganese atoms to iron atoms in the manganese iron lithium oxide is W, 0.4≤W≤1.5. Exemplarily, the molar ratio of manganese atoms to iron atoms in the manganese iron lithium oxide may be any one of 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5 or a range between any two values. The molar ratio of manganese atoms to iron atoms in the manganese iron lithium oxide is within the above range, and the manganese iron lithium oxide has a suitable manganese platform capacity ratio, thereby improving the kinetic performance.

[0038] In some embodiments, the conductive polymer includes at least one of polyethylene succinate, polyethylene oxide, polyethylene glycol imine, and polypyrrole. Using the conductive polymer described in the present application, the shell layer formed on the surface of the manganese iron lithium oxide has flexibility and manufacturability, and the core-shell structure can also effectively improve the active ion conductivity and electrical conductivity of the positive electrode material.

[0039] In some embodiments, the manganese iron lithium oxide contains Mg element and Ti element, and the content of Mg element in the manganese iron lithium oxide is greater than the content of Ti element in the manganese iron lithium oxide.

[0040] In some embodiments, the manganese iron lithium oxide contains Mg and Ti elements, the content of the Mg element is Appm, the content of the Ti element is B ppm, and satisfies: A / B≤10.3. Exemplarily, the A / B can be any one of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10.3 or a range between any two values. The doping amounts of the Mg and Ti elements satisfying the above relationship can not only improve the conductivity of the manganese iron lithium oxide, but also increase the unit cell parameters and improve the lithium ion diffusion rate, thereby further reducing the polarization of the charge and discharge process and reducing the duration of constant voltage charging.

[0041] In some embodiments, the manganese iron lithium oxide contains Mg and Ti elements, the content of the Mg element is Appm, the content of the Ti element is B ppm, and the following relationship is satisfied: 1.3≤A / B≤8.

[0042] In some embodiments, the content of the Mg element is A ppm, 2400≤A≤3100. Exemplarily, the content of the Mg element may be any one of 2400ppm, 2500ppm, 2600ppm, 2700ppm, 2800ppm, 2900ppm, 3000ppm, 3100ppm, or a range between any two values.

[0043] In some embodiments, the content of the Ti element is B ppm, 300≤B≤1800. Exemplarily, the content of the Ti element can be any one of 300ppm, 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1100ppm, 1200ppm, 1300ppm, 1400ppm, 1500ppm, 1600ppm, 1700ppm, 1800ppm, or a range between any two of the values.

[0044] In some embodiments, the secondary battery includes a positive electrode plate, the positive electrode plate includes a current collector and a positive electrode active material layer disposed on at least one side of the current collector, the positive electrode active material layer includes a positive electrode active material, the positive electrode active material includes manganese iron lithium oxide and a coating layer containing a conductive polymer disposed on at least a portion of the surface of the manganese iron lithium oxide, the manganese iron lithium oxide contains Mg element and Ti element, the content of the Mg element is A ppm, the content of the Ti element is B ppm, satisfying: 1.3≤A / B≤8.

[0045] A groove is provided on the surface of the positive electrode active material layer away from the current collector along the thickness direction of the positive electrode sheet;

[0046] The positive electrode sheet satisfies: 0.03≤K≤0.37, K=δ×P / D / W 2 ;

[0047] Wherein, Dμm is the Dv50 of the manganese iron lithium oxide;

[0048] P μm is the depth of the groove in the positive electrode active material layer;

[0049] δμm is the thickness of the coating layer;

[0050] W is the molar ratio of manganese atoms to iron atoms in the manganese iron lithium oxide.

[0051] By controlling the content ratio of Mg and Ti in manganese iron lithium oxide within the range described in the present application, and simultaneously regulating the particle size of manganese iron lithium oxide, manganese iron ratio, thickness of the surface high-kinetic conductive polymer coating layer and depth of the grooves in the positive electrode active material layer, so that these parameters satisfy the relationship described in the present application, the kinetic performance of the secondary battery can be further improved, thereby further reducing the cycle charging time, and ultimately improving the gas production performance and cycle performance of the secondary battery.

[0052] In some embodiments, the porosity of the positive electrode sheet is 15-25%. Exemplarily, the porosity of the positive electrode sheet is any one of 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, or a range between any two values. When the porosity of the positive electrode sheet is within this range, the wettability of the sheet can be improved and a higher compaction density can be maintained, thereby improving the dynamic performance and ensuring the energy density.

[0053] In some embodiments, the compaction density of the positive electrode sheet is 2.2 to 2.4 g / cm 3 For example, the compaction density of the positive electrode sheet may be 2.2 g / cm 3 , 2.3g / cm 3 , 2.4g / cm3 Any value or range between any two values ​​in .

[0054] In some embodiments, the groove refers to a groove stripe produced along the width direction of the positive electrode plate after the surface of the positive electrode plate is laser etched.

[0055] In some embodiments, the distance between any two adjacent grooves is 0.5 mm to 2.0 mm. When the distance between adjacent grooves is within the above range, a high energy density can be maintained while maintaining the kinetic performance of the secondary battery.

[0056] In some embodiments, the secondary battery further comprises a negative electrode sheet, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material.

[0057] The type of negative electrode active material is not specifically limited and can be selected according to actual needs. For example, the negative electrode material can be artificial graphite, natural graphite, silicon-carbon composite material, silicon oxide, hard carbon, lithium metal and lithium titanate.

[0058] The type of negative electrode current collector is not particularly limited and can be selected according to actual needs. Preferably, copper foil or carbon-coated copper foil can be used.

[0059] In some embodiments, the secondary battery further comprises a separator. The type of separator is not particularly limited and can be selected according to actual needs. The separator can be a polypropylene film, a polyethylene film, a polyvinylidene fluoride, a spandex film, an aramid film, or a multilayer composite film modified by a coating.

[0060] In some embodiments, the preparation of a secondary battery includes: stacking the positive electrode sheet, the separator, and the negative electrode sheet in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then winding them into a square bare cell, loading them into a battery casing, and then baking them at 65 to 95°C to remove water, injecting electrolyte, sealing, and obtaining a secondary battery after standing, hot and cold pressing, formation, clamping, capacity division and other processes.

[0061] In some embodiments, the secondary battery may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package, and the material of the soft package may be plastic, such as polypropylene.

[0062] In some embodiments, the shape of the secondary battery is not particularly limited, and it can be cylindrical, square, or any other shape.

[0063] The second aspect of the present application provides an electric device, which includes the secondary battery described in the first aspect of the present application. The electric device can be an application device such as a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy, and an electric tool. The vehicle can be a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle, or an extended-range vehicle, etc.; the spacecraft includes an airplane, a rocket, a space shuttle, and a spacecraft, etc.; the electric toy includes a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy, etc.; the electric tool includes a metal cutting electric tool, a grinding electric tool, an assembly electric tool, and a railway electric tool, such as an electric drill, an electric grinder, an electric wrench, an electric screwdriver, an electric hammer, an impact drill, a concrete vibrator, and an electric planer, etc. The embodiments of the present application do not impose any special restrictions on the above-mentioned devices.

[0064] The following are specific embodiments of the present application, and the technical scheme of the present application is further described in conjunction with the embodiments, but the present application is not limited to these embodiments. The reagents, methods and equipment used in the present application, unless otherwise specified, are conventional reagents, methods and equipment in the art.

[0065] Example 1

[0066] Embodiment 1 provides a secondary battery, and the specific preparation process of the secondary battery includes:

[0067] (1) Preparation of positive electrode active materials

[0068] S11. Lithium carbonate, manganese sulfate, ferrous sulfate, ammonium dihydrogen phosphate, magnesium oxide, and titanium dioxide are added to a ball mill according to a molar ratio of 0.5:0.5:0.5:1:0.018:0.003, and then ball-milled for 24 hours to obtain a precursor; the precursor is placed in a tubular furnace for calcination, first heated to 350°C at a heating rate of 3°C / min for pre-calcination for 240 minutes, then heated to 700°C at a heating rate of 5°C / min, calcined for 640 minutes, and naturally cooled to obtain LiMn containing Mg and Ti elements. 0.5 Fe 0.5 PO4;

[0069] S12. Weigh LiMn containing Mg and Ti elements 0.5 Fe 0.5 PO4 and conductive polymer, the conductive polymer is polyethylene succinate, LiMn 0.5 Fe 0.5 The mass ratio of PO4 and conductive polymer is 90:10, and LiMn 0.5 Fe 0.5PO4 and conductive polymer were mixed and heated to 200℃ for 12 hours in a nitrogen atmosphere to melt the conductive polymer and form a conductive layer on the LiMn 0.5 Fe 0.5 A coating layer is formed on the surface of PO4 to obtain LiMn coated with a conductive polymer. 0.5 Fe 0.5 PO4 materials, including LiMn 0.5 Fe 0.5 The thickness of the conductive polymer coated on the PO4 surface is 4 nm.

[0070] (2) Preparation of positive electrode sheet

[0071] S21. The prepared positive electrode active material, conductive agent (conductive carbon black), and binder (polyvinylidene fluoride, PVDF) are mixed in a mass ratio of 96.3:2:1.7, and then stirred and mixed with a solvent (1-methyl-2-pyrrolidone, NMP) to obtain a positive electrode slurry, and then the positive electrode slurry is coated on both sides of an aluminum foil, and a positive electrode sheet is obtained through a baking and rolling process;

[0072] S22. The positive electrode plate is introduced into a laser drilling machine, and a groove is formed by laser etching 15 μm below the surface of the plate. The grooves are evenly distributed and continuously repeated on the surface of the plate, and the spacing between adjacent grooves is 1 mm.

[0073] (3) Preparation of negative electrode sheet

[0074] The negative electrode active material graphite, conductive agent carbon black, dispersant (CMC) and binder (SBR) are mixed in a mass ratio of 97:0.6:0.9:1.5, deionized water is added and stirred at high speed to disperse evenly, and the slurry viscosity is adjusted to 4000cps to obtain a negative electrode slurry; then the prepared negative electrode slurry is sieved with a 150-mesh double-layer filter cloth, and extrusion-coated on the upper and lower surfaces of a 4.5μm copper foil. During the coating process, the electrode is heated and dried in an oven, and then cold pressed, slit and cut to obtain a negative electrode sheet.

[0075] (4) Preparation of electrolyte

[0076] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) are mixed in a volume ratio of 1.2:0.8:1 to obtain an organic solvent, the solute lithium salt is lithium hexafluorophosphate (LiPF6), and the above mixed organic solvent is added to prepare an electrolyte with a concentration of 1.2 mol / L.

[0077] (5) Preparation of secondary batteries

[0078] The positive electrode sheet, the isolation film (composed of 7μm polyethylene-based film + single-sided 2μm ceramic coating + single-sided 5μm polyvinylidene fluoride organic coating), and the negative electrode sheet are assembled into a roll core by winding, and then transferred into an aluminum-plastic film; the finished battery is obtained through processes such as liquid injection, packaging, standing, formation, aging, and capacity division.

[0079] Embodiments 2 to 5

[0080] The difference between Examples 2 to 5 and Example 1 is that the depths of the grooves formed by laser etching downward on the surface of the pole piece are different, namely 13 μm, 14 μm, 16 μm and 17 μm.

[0081] Embodiments 6 to 11

[0082] The difference between Examples 6 to 11 and Example 1 is that the Dv50 of the positive electrode active material is different, which are 0.7μm, 0.8μm, 1μm, 1.1μm, 1.2μm, and 1.3μm, respectively. The difference between the specific preparation method and Example 1 is that the high-temperature calcination temperatures are 740℃, 720℃, 690℃, 680℃, 670℃, and 660℃, respectively, and the calcination times are 800min, 720min, 640min, 600min, 560min, and 520min, respectively.

[0083] Embodiments 12 to 14

[0084] The difference between Examples 12 to 14 and Example 1 is that the manganese-iron ratio of the positive electrode material lithium manganese iron phosphate is different, and the manganese-iron ratio is 6:4, 4:6, and 3:7 respectively. The specific preparation method is different from Example 1 in that the ratio of manganese sulfate to ferrous sulfate in the raw materials is 6:4, 4:6, and 3:7 respectively.

[0085] Embodiments 15 to 18

[0086] The difference between Examples 15 to 18 and Example 1 is that the thickness of the conductive polymer layer coated on the surface of the positive electrode active material is different, which are 2nm, 3nm, 5nm, and 6nm respectively. The difference between the specific preparation method and Example 1 is that the mass ratios of lithium manganese iron phosphate nanomaterial and conductive polymer in the raw materials are 96:4, 93:7, 87:13, and 84:16 respectively.

[0087] Examples 19 to 21

[0088] In Examples 19 to 21, the contents of Mg and Ti in the positive electrode active material are adjusted by adjusting the molar ratio of the raw materials in the positive electrode active material. The specific contents of Mg and Ti are shown in Table 1.

[0089] Comparative Example 1

[0090] The difference between Comparative Example 1 and Example 1 is that the surface of the lithium manganese iron phosphate positive electrode is not coated with a conductive polymer.

[0091] Comparative Example 2

[0092] The difference between Comparative Example 2 and Example 1 is that the positive electrode plate is not laser etched to form a groove.

[0093] Comparative Example 3

[0094] The difference between Comparative Example 3 and Example 1 is that the depth of the groove on the surface of the laser-etched pole piece is 10 μm; the manganese to iron ratio of the positive electrode material lithium manganese iron phosphate is 2:8, and the specific preparation method is different from Example 1 in that the ratio of manganese sulfate to ferrous sulfate in the raw materials is 2:8.

[0095] Comparative Example 4

[0096] The difference between Comparative Example 4 and Example 1 is that the positive electrode active material does not contain Mg and Ti elements. The steps of the preparation method of the positive electrode active material are as follows:

[0097] S11. Lithium carbonate, manganese sulfate, ferrous sulfate, and ammonium dihydrogen phosphate were added to a ball mill in a molar ratio of 0.5:0.5:0.5:1, and then ball-milled for 24 hours to obtain a precursor; the precursor was placed in a tubular furnace and calcined, firstly heated to 350°C at a heating rate of 3°C / min for pre-calcination for 240 minutes, then heated to 700°C at a heating rate of 5°C / min, calcined for 640 minutes, and naturally cooled to obtain LiMn 0.5 Fe 0.5 PO4;

[0098] S12. Weigh LiMn 0.5 Fe 0.5 PO4 and conductive polymer, the conductive polymer is polyethylene succinate, LiMn 0.5 Fe 0.5 The mass ratio of PO4 and conductive polymer is 90:10, and LiMn 0.5 Fe 0.5 PO4 and conductive polymer were mixed and heated to 200℃ for 12 hours in a nitrogen atmosphere to melt the conductive polymer and form a conductive layer on the LiMn 0.5 Fe 0.5 A coating layer is formed on the surface of PO4 to obtain LiMn coated with a conductive polymer. 0.5 Fe 0.5 PO4 materials, including LiMn 0.5 Fe 0.5 The thickness of the conductive polymer coated on the PO4 surface is 4 nm.

[0099] The parameters of the manganese iron lithium oxide and the positive electrode sheet in Examples 1 to 21 and Comparative Examples 1 to 4 are shown in Table 1.

[0100] The cycle performance and gas generation performance of the secondary batteries prepared in the embodiments and comparative examples were tested, and the results are shown in Table 2.

[0101] The test method for cycle performance is:

[0102] At 45±0.5℃, the charge and discharge test was carried out using a charge and discharge test system. The charge and discharge conditions were:

[0103] 1.1C constant current charge to 4.25V, then constant voltage charge to 0.05C;

[0104] 2. Leave for 30 minutes;

[0105] 3.1.0C constant current discharge to 2.5V;

[0106] 4. Leave for 30 minutes;

[0107] 5. Repeat steps 2 to 5 for 500 cycles.

[0108] Among them, the constant voltage charging time can be recorded by the tester; the capacity retention rate is obtained by dividing the capacity after 500 cycles by the initial battery capacity.

[0109] The gas production of the battery cycle is obtained by testing the volume of the battery before and after the cycle using the water displacement method. The specific steps are as follows:

[0110] 1. Preparation stage: First prepare a beaker and ensure that it can accurately measure the volume change of the liquid in the beaker;

[0111] 2. Initial measurement: record the initial volume of liquid in the container, recorded as V1;

[0112] 3. Battery immersion: Tie the battery to be tested with a thin wire and then slowly immerse it in the liquid in the beaker;

[0113] 4. Final measurement: When the battery is completely immersed in the liquid, record the volume of the liquid in the beaker again and record it as V2;

[0114] 5. Calculate the volume: By calculating the volume difference of the liquid before and after immersion in the battery, that is, V2-V1, the gas production of the battery cycle is obtained.

[0115] Table 1

[0116]

[0117]

[0118] Table 2

[0119] Cyclic constant voltage charging time (min) Gas production after 500 cycles (ml) Capacity retention rate after 500 cycles (%) Comparative Example 1 6.47 4.62 90.31 Comparative Example 2 6.12 4.07 90.65 Comparative Example 3 7.18 5.42 89.62 Comparative Example 4 6.23 4.45 90.22 Example 1 5.36 2.68 91.75 Example 2 5.81 2.91 91.34 Example 3 5.62 2.81 91.56 Example 4 5.18 2.35 91.94 Example 5 5.01 2.19 92.35 Example 6 4.92 2.02 92.01 Example 7 5.15 2.24 91.87 Example 8 5.51 2.85 91.66 Example 9 5.66 2.97 91.51 Example 10 5.79 3.09 91.46 Embodiment 11 5.91 3.28 91.41 Example 12 6.02 3.49 91.28 Embodiment 13 4.27 2.05 92.45 Embodiment 14 3.24 1.42 93.51 Embodiment 15 5.81 2.94 91.43 Example 16 5.57 2.75 91.61 Embodiment 17 5.25 2.51 91.86 Embodiment 18 5.19 2.46 91.92 Embodiment 19 5.74 2.77 91.39 Embodiment 20 5.76 2.81 91.33 Embodiment 21 5.91 3.01 91.16

[0120] From the above embodiments and comparative examples, by reasonably regulating the particle size of manganese iron lithium oxide containing Mg element and / or Ti element, the manganese iron ratio, the thickness of the surface high dynamics conductive polymer coating layer and the depth of the grooves in the positive electrode active material layer, the above parameters are made to satisfy a specific relationship, which significantly reduces the cyclic constant voltage charging time of the secondary battery and improves the gas production performance and cycle performance of the secondary battery.

[0121] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A secondary battery, characterized in that: The invention comprises a positive electrode plate, wherein the positive electrode plate comprises a current collector and a positive electrode active material layer disposed on at least one side of the current collector, wherein the positive electrode active material layer comprises a positive electrode active material, wherein the positive electrode active material comprises manganese iron lithium oxide and a coating layer containing a conductive polymer disposed on at least a portion of the surface of the manganese iron lithium oxide, wherein the manganese iron lithium oxide contains Mg element and / or Ti element; A groove is provided on the surface of the positive electrode active material layer away from the current collector along the thickness direction of the positive electrode sheet; The positive electrode sheet satisfies: 0.03≤K≤0.37, K=δ×P / D / W 2 ; Wherein, Dμm is the Dv50 of the manganese iron lithium oxide; P μm is the depth of the groove in the positive electrode active material layer; δμm is the thickness of the coating layer; W is the molar ratio of manganese atoms to iron atoms in the manganese iron lithium oxide.

2. The secondary battery according to claim 1, characterized in that: 0.7≤D≤1.3。 3. The secondary battery according to claim 1, characterized in that: 13≤P≤17。 4. The secondary battery according to claim 1, characterized in that: 0.002≤δ≤0.

006.

5. The secondary battery according to claim 1, characterized in that: 0.4≤W≤1.5。 6. The secondary battery according to claim 1, characterized in that: The conductive polymer includes at least one of polyethylene succinate, polyethylene oxide, polyethylene glycol imine, and polypyrrole.

7. The secondary battery according to claim 1, characterized in that: The manganese iron lithium oxide contains Mg and Ti elements, the content of the Mg element is Appm, the content of the Ti element is B ppm, and the relationship A / B≤10.3 is satisfied.

8. The secondary battery according to claim 1 or 7, characterized in that: The content of the Mg element is Appm, 2400≤A≤3100.

9. The secondary battery according to claim 1 or 7, characterized in that: The content of the Ti element is B ppm, 300≤B≤1800.

10. An electrical device, characterized in that: The electrical equipment comprises the secondary battery according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Positive electrode active substance and preparation method thereof, positive electrode material containing positive electrode active substance and battery

    CN105810940A

  • Lithium manganese iron phosphate positive electrode material, preparation method and application thereof

    CN115832257A

  • Secondary battery and electric equipment comprising same

    CN116169339A

  • Rapid preparation method of spherical lithium iron manganese phosphate positive electrode material

    CN116216685A

  • Secondary battery and electric equipment

    CN116314601A